A microRNA‐129‐5p/Rbfox crosstalk coordinates homeostatic downscaling of excitatory synapses. (9th May 2017) - Rajman, Marek; Metge, Franziska; Fiore, Roberto; Khudayberdiev, Sharof; Aksoy‐Aksel, Ayla; Bicker, Silvia; Ruedell Reschke, Cristina; Raoof, Rana; Brennan, Gary P; Delanty, Norman; Farrell, Michael A; O'Brien, Donncha F; et al.
Abstract: Synaptic downscaling is a homeostatic mechanism that allows neurons to reduce firing rates during chronically elevated network activity. Although synaptic downscaling is important in neural circuit development and epilepsy, the underlying mechanisms are poorly described. We performed small RNA profiling in picrotoxin (PTX)‐treated hippocampal neurons, a model of synaptic downscaling. Thereby, we identified eight microRNAs (miRNAs) that were increased in response to PTX, including miR‐129‐5p, whose inhibition blocked synaptic downscaling in vitro and reduced epileptic seizure severity in vivo . Using transcriptome, proteome, and bioinformatic analysis, we identified the calcium pump Atp2b4 and doublecortin (Dcx) as miR‐129‐5p targets. Restoring Atp2b4 and Dcx expression was sufficient to prevent synaptic downscaling in PTX‐treated neurons. Furthermore, we characterized a functional crosstalk between miR‐129‐5p and the RNA‐binding protein (RBP) Rbfox1. In the absence of PTX, Rbfox1 promoted the expression of Atp2b4 and Dcx. Upon PTX treatment, Rbfox1 expression was downregulated by miR‐129‐5p, thereby allowing the repression of Atp2b4 and Dcx. We therefore identified a novel activity‐dependent miRNA/RBP crosstalk during synaptic scaling, with potential implications for neural network homeostasis and epileptogenesis. Synopsis: A systematic approach using small RNA and mRNA profiling in combination with proteomics is used to delineate post‐transcriptional regulatory pathways involved in synaptic scaling. This led to the identification of a pathway consisting of the miRNA miR‐129‐5p and the RNA‐binding protein Rbfox that controls excitatory synapse function in neurons and epileptic seizure activity in the brain. 8 microRNAs, including miR‐129‐5p, are upregulated during homeostatic synaptic downscaling in hippocampal neurons. miR‐129‐5p inhibition blocks synaptic downscaling in vitro and kainic acid‐induced epileptic seizures in vivo . A combination of transcriptomics, proteomics and bioinformatics was used to identify miR‐129‐5p target mRNAs, including Atp2b4, Dcx and Rbfox1/3 . Activity‐dependent downregulation of Rbfox1 by miR‐129‐5p is required for the repression of synaptic genes during homeostatic synaptic downscaling. Abstract : Combining miRNA and mRNA profiling with proteomics reveals roles for miR‐129‐5p and the RNA‐binding protein Rbfox in excitatory synapse function and epileptic seizure.